![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Câu C
tách:
SSH:(20-2):1+1=19
Tổng:(20+2).19:2=209
C=4209
Câu:B
Tách:
SSH:(202-1):1+1=202
Tổng:(202+1).202:2=20503
B=320503
![](https://rs.olm.vn/images/avt/0.png?1311)
a , 35 - ( 5 - 18 ) + ( - 17 )
= 35 - 5 + 18 - 17
= 30 + 18 - 17
= 48 - 17
= 31
b , 62 : 4 . 3 + 2 . 52 - 2010
= 36 : 4 . 3 + 2 . 25 - 1
= 9 . 3 + 2 . 25 - 1
= 27 + 50 - 1
= 77 - 1
= 76
![](https://rs.olm.vn/images/avt/0.png?1311)
a) Đặt A = 21 + 22 + 23 +....+299 + 2100
=> 2A = 2+ 22 + 23 +...+2100 + 2101
=> 2A - A = 2 + 22 + 23 +...+2100 + 2101 - (1+2+22+23+...+299+2100)
=> A = 2 + 22 + 23 +...+ 2100 +2101 -1 - 2 - 22 - 23 -...- 299 - 2100
= 2101 -1
Vậy....
b) B = 2 + 23 + 25 + ... + 22013
4B = 23 + 25 + 27 + ... + 22015
4B - B = (23 + 25 + 27 + ... + 22015) - (2 + 23 + 25 + ... + 22013)
3B = 22015 - 2
B = \(\dfrac{2^{2015}-2}{3}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
4C=43+44+45+...+4202+4203
4C-C=(43+44+45+...+4202+4203)-(42+43+44+...+4201+4202)
3C=4203-42
C=(4203-42):3
![](https://rs.olm.vn/images/avt/0.png?1311)
B=3+32+33+....+3201+3202
3B= 32+33+....+3201+3202+3203
3B-B= (32+33+....+3201+3202+3203) - (3+32+33+....+3201+3202)
2B= 3203 - 3
B= (3203 - 3) :2
Vậy B= (3203 - 3) :2
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 315+( 146-x)=401
146 - x = 401 - 315
146 - x = 86
x = 146 - 86
x = 60
b) (6x -39) :3 = 201
(6.x -39) = 201x3
(6.x -39) = 603
6.x = 603+39
6.x = 642
x = 624:6
x = 107
c) 23+ 3x = 56:53
23+ 3x =53
23+ 3x = 125
3x = 125 - 23
3x = 102
x = 102:3
x = 34
d) 9x-1 = 9
9x-1 = 91
Suy ra: x-1 =1
x = 1+1
x = 2
e) x4 = 16
x4 = 24
Suy ra: x = 2
f) 2x : 25 = 1
2x = 1x 25
2x = 25
Suy ra : x =5
g) 2x + 1 . 22014 = 22015
2x + 1 = 22015 : 22014
2x + 1 = 2
2x = 2 - 1
x = 1:2
x = \(\frac{1}{2}\)
Ta có : \(2S=2^2+2^3+2^4+...+2^{201}\)
\(< =>S=2+2^2+2^3+...+2^{200}\)
Nên \(2S-S=\left(2^2+2^3+2^4+...+2^{201}\right)-\left(2+2^2+2^3+...+2^{200}\right)\)
\(< =>S=2^{201}-2< =>2S=2^{202}-4\)
Vậy \(2S=2^2+2^3+2^4+...+2^{201}=2^{202}-4\)
s2=2 mũ 202 -4